Valuasi Ekonomi Taman Nasional Ujung Kulon - Erwin Prayogi; Indah Susilowati; Mukson Mukson (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
The integrated development of tourism is done through cross-sectoral coordination so that the development can make a huge stride. The goals of this study are to estimate the economic valuations to measure the ability/willingness to pay of visitors; to analyze the prospects of fisheries resources management in Ujung Kulon National Park; and to formulate marine tourism model of Ujung Kulon National Park. This study was conducted on the 1.619,68 Ha area of utilization zones in Ujung Kulon National Park, covering 1.518,91 Ha land area and 100,77 Ha of water area. The used study method was survey method which was quantitative and qualitative along with questionnaires as the instrument. Purposive sampling method was applied to collect data. Data analysis used was economic surplus and willingness to pay. The result obtained was the demand of marine recreation at utilization zones in Ujung Kulon National Park was determined by cost of travel, length of visit and education. The total value of Willingness to Pay in one year was Rp 512.898.500,00. The mentioned value was the projected value of willingness and ability of people to pay for conservation area of the marine protected area and marine tourism in Ujung Kulon. The goals of marine tourism that had been enacted by people was then coordinated with central government. The process of marine tourism development was expected to be able to positively improve other regional development. The outcome of the study was hoped to provide improvement on marine tourism management at Ujung Kulon National Park Keywords: tourism, marine, Ujung Kulon National Park